The Effects of High-intensity Functional Training (HIFT) on Spatial Learning, Visual Pattern Separation and Attention Span in Adolescents - Ben-Zeev, Tavor; Hirsh, Tamir; Weiss, Inbal; Gornstein, Michael; Okun, Eitan (Frontiers in Behavioral Neuroscience, 2020)
Aerobic, anaerobic, and strength exercises are known to improve various cognitive functions, such as executive functions, pattern separation, and working memory. High-Intensity Functional Training (HIFT) is a form of physical activity that can be modified to any fitness level and elicits greater muscle recruitment than repetitive aerobic exercises, thereby improving cardiovascular endurance, strength, and flexibility. HIFT emphasizes functional, multi-joint movements via high-intensity interval training (HIIT) and muscle-strengthening exercises. It is yet unknown, however, whether HIFT affects cognitive functions in adolescents. In order to address this question, we subjected adolescents to 3x20min training sessions/week of HIFT for 3 months. The effects of HIFT were tested on performance in: (1) virtual reality (VR)-based spatial learning task, (2) computerized visual pattern separation, and (3) attention span. The control group performed a typical physical class 3 times per week. The effects on cognition were tested at baseline and following 3 months of HIFT. Three months into the intervention, the HIFT group achieved higher scores in the spatial learning task, pattern separation task, and in the attention span test, compared with controls. These data suggest that HIFT can potentially translate into improving school performance in adolescents.